L1-Norm and L An Introduction to the Least Absolute Residuals, the Minimax Absolute Residual and Related Fitting Procedures - Farebrother, Richard William. (SpringerBriefs in Statistics, 2013)
This monograph is concerned with the fitting of linear relationships in the context of the linear statistical model. As alternatives to the familiar least squared residuals procedure, it investigates the relationships between the least absolute residuals, the minimax absolute residual and the least median of squared residuals procedures. It is intended for graduate students and research workers in statistics with some command of matrix analysis and linear programming techniques.